THE USEFULNESS OF IMPLEMENTING CONCEPTS OF DEVOTION TO THE MOTHERLAND IN PREPARING STUDENTS FOR MILITARY SERVICE THROUGH THE ELEMENTS OF INITIAL PREPARATION (Scientific journal of the Fergana State University, 2023)
In this article, the acquisition of military knowledge of students is of great importance in the formation of a person. Because, along with forming a sense of responsibility and discipline in a student, military education trains him physically and mentally and sharpens his will. It educates students in a comprehensive, patriotic spirit. Military education is considered the main factor in the formation of the sense of responsibility to the Motherland and the feeling of loyalty to the Motherland. In addition, it awakens national identity, patriotism, and a desire to learn. The basis of these feelings is formed during military training.